Biomechanically Preferred Consonant-Vowel Combinations Fail to Appear in Adult Spoken Corpora - Whalen, D. H. (2012)
Certain consonant/vowel (CV) combinations are more frequent than would be expected from the individual C and V frequencies alone, both in babbling and, to a lesser extent, in adult language, based on dictionary counts: Labial consonants co-occur with central vowels more often than chance would dictate; coronals co-occur with front vowels, and velars with back vowels (Davis & MacNeilage, 1994). Plausible biomechanical explanations have been proposed, but it is also possible that infants are mirroring the frequency of the CVs that they hear. As noted, previous assessments of adult language were based on dictionaries; these “type” counts are incommensurate with the babbling measures, which are necessarily “token” counts. We analyzed the tokens in two spoken corpora for English, two for French and one for Mandarin. We found that the adult spoken CV preferences correlated with the type counts for Mandarin and French, not for English. Correlations between the adult spoken corpora and the babbling results had all three possible outcomes: significantly positive (French), uncorrelated (Mandarin), and significantly negative (English). There were no correlations of the dictionary data with the babbling results when we consider all nine combinations of consonants and vowels. The results indicate that spoken frequencies of CV combinations can differ from dictionary (type) counts and that the CV preferences apparent in babbling are biomechanically driven and can ignore the frequencies of CVs in the ambient spoken language.